Health insurance and diversity of treatment : a policy mix perspective (2013)
We determine the optimal health policy mix when the average utility of patients increases with the supply of drugs available in a therapeutic class. Health risk coverage rely on two instruments, copayment and reference pricing, that affect the supported risk composed by health expenses and diversity of treatment. For a fixed supply of drugs, the reference pricing policy aims at minimizing expenses in which case, the equilibrium price of drugs is independent of the copayment rate. However, with endogenous supply of drugs, diversity of treatment may susbtitute for insurance so that the reference pricing may depart from maximal cost-containement to promote entry. We then analyse the determinents of the optimal policy. While an increase in risk aversion or in the side effect loss increases diversity and decreases the copayment rate, an increase in entry cost both decreases diversity and the copayment rate.